A regular thymine tetrad and a peculiar supramolecular assembly in the first crystal structure of an all‐LNA G‐quadruplex. (1st February 2014) - Russo Krauss, Irene; Parkinson, Gary Nigel; Merlino, Antonello; Mattia, Carlo Andrea; Randazzo, Antonio; Novellino, Ettore; Mazzarella, Lelio; Sica, Filomena
<x xml:space="preserve">Abstract</x> Locked nucleic acids (LNAs) are formed by bicyclic ribonucleotides where the O2′ and C4′ atoms are linked through a methylene bridge and the sugar is blocked in a 3′‐endo conformation. They represent a promising tool for therapeutic and diagnostic applications and are characterized by higher thermal stability and nuclease resistance with respect to their natural counterparts. However, structural descriptions of LNA‐containing quadruplexes are rather limited, since few NMR models have been reported in the literature. Here, the first crystallographically derived model of an all‐LNA‐substituted quadruplex‐forming sequence 5′‐TGGGT‐3′ is presented refined at 1.7 Å resolution. This high‐resolution crystallographic analysis reveals a regular parallel G‐quadruplex arrangement terminating in a well defined thymine tetrad at the 3′‐end. The detailed picture of the hydration pattern reveals LNA‐specific features in the solvent distribution. Interestingly, two closely packed quadruplexes are present in the asymmetric unit. They face one another with their 3′‐ends giving rise to a compact higher‐order structure. This new assembly suggests a possible way in which sequential quadruplexes can be disposed in the crowded cell environment. Furthermore, as the formation of ordered structures by molecular self‐assembly is an effective strategy to obtain nanostructures, this study could open the way to the design of a new class of LNA‐based building blocks for nanotechnology.